Semantics of the Church Image in the Spatiotemporal Worldbuilding of Short-story Collections by Nikolai Vasilievich Gogolâ€ Evenings on a Farm Near Dikankaâ€ and â€œMirgorodâ€ - Pavelieva, Anna; Kushnirova, Tetiana; Dmytrenko, Olena; Sherstiuk, Nataliia (International Journal of Engineering and Technology, 2018)
The article deals with the peculiarities of churchesâ€™ depiction, semantics and functions of the church image in the cycles by Nikolai Gogol â€Evenings on a Farm Near Dikankaâ€ and â€œMirgorodâ€. In particular, there have been considered meaning-making, plot-creating, image-creating functions of the church image in the first Gogolian collected stories. The authors of the article have analyzed the place of the church in the spatiotemporal worlbuilding either of every tale separately, or of both collections altogether, comparing and contrasting the images of church in different stories. There have also been taken into account the allocation and role of the church in the human realm (as opposed to the space axes of the demoniac world), as a bastion of hope, the noise and colour saturation of the church space. This article also considers decline in sacredness, representation of the church as household, carnal and fleshy space as a symbol of the moral lapse, spiritual and moral fall of the characters, the deformation of their inner (spiritual) space. The church is examined as the key image of the short-story â€œViyâ€. The peculiarities of representation of faith, different Christian traditions, various kinds of temples are explained in relation with the plot, the characters and the key motives of every tale.Â Â